Nano Medicine in Healing Chronic Wounds: Opportunities and Challenges - Khan, Soban; Rai, Vishal; Srivastava, Saurabh; Agarwal, Srashti; Bano, Nausheen; Gupta, Yash (Journal for Research in Applied Sciences and Biotechnology, 2024)
Chronic wounds pose a continual healthcare challenge, demanding innovative interventions to improve healing outcomes. This comprehensive review navigates the transformative landscape of nanotechnology in chronic wound healing, covering mechanisms, clinical applications, challenges, and future directions. The introduction establishes the need for advanced therapeutic strategies, providing an overview of chronic wounds and the evolving landscape of therapeutic approaches. The exploration of nanoparticle types and their mechanisms in wound healing encompasses lipid-based, polymeric, and inorganic variants, each contributing uniquely to drug solubility, controlled release, and tailored interactions within the wound microenvironment. Clinical applications and formulations exemplify real-world efficacy, demonstrating nanotechnology's success in promoting wound healing. Opportunities in nano-medicine for chronic wounds focus on targeted drug delivery precision and overcoming cellular barriers through enhanced cellular uptake. Acknowledging challenges, including biocompatibility concerns and regulatory hurdles, the review emphasizes the need for rigorous evaluation and streamlined regulatory pathways. Future directions delve into emerging nanotechnologies and potential breakthroughs, highlighting advancements in design, fabrication, and integration with artificial intelligence and personalized medicine.